Drug use and its associated factors among pregnant women in Bahir Dar city administration, northwest Ethiopia - Endalkachew Worku Mengesha (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2019)
Background: The use of drugs during pregnancy calls for special attention because the health and life of unborn child has great value in addition to the mother. The drugs given to pregnant mothers for therapeutic purposes may cause serious structural and functional adverse effects in the developing child. The aim of this study was to assess drug use and its associated factors among pregnant women in Bahir Dar city administration. Methods: Institutional based cross sectional study design was carried out. Data were entered into epi.info version 7 and analyzed using SPSS version 20. Crude and adjusted odds ratio were estimated to identify the associated factors using multivariable logistic regression.